Concurrent validation of the MABC-2 motor tests and MABC-2 checklist according to the developmental coordination disorder questionnaire-BR - Capistrano R.* (2015)
The Movement Assessment Battery for Children, 2nd Ed (MABC-2), comprised of motor tests and a questionnaire (Checklist), has been used by several nationalities to identify problems in children's motor behavior. However, the level of agreement between the motor tests and the checklist has been questioned. So, this study aimed to test the level of competition between the MABC-2 motor test and MABC-2 Checklist, controlled by the Developmental Coordination Disorder Questionnaire (DCDQ-BR) as the gold reference. Parents of 40 children and 16 teachers responded to the MABC-2 Checklist and the DCDQ-BR. Later 40 children were evaluated using the MABC-2 motor test. No significant congruence among a comparison of the MABC-2 motor tests, MABC-2 Checklist and DCD-Q-BR was observed. The results indicated that there is no concurrent validity between the MABC-2 motor tests and the DCDQ-BR test, whereas the MABC-2 Checklist showed low levels of concurrent validity with the DCDQ-BR.